Hubungan Pemikiran Politik Ikhwanul Muslimin dengan Aktivitas Kesatuan Aksi Mahasiswa Muslim Indonesia - Rahmadani, Suci; Arifin, Adil (Universitas Sumatera Utara, 2018)
This study is about the relationship political thought of the Ikhwanul Muslimin to KAMMI organization activities region north of sumatera. The focuss of the study is review about how much the relationship between political though of the Ikhwanul Muslimin to KAMMI Organization activities region north of Sumatera. The conclution of the studi is there is a relationship between political thought of Ikhwanul Muslimin to KAMMI organization activities region north of Sumatera, as the books of the Ikhwanul Muslimin leaders be required reading to KAMMI, than KAMMI tarbiyah activity in accordance with the concept of establishing an Islamic state of IM.Â Next, The result of the study with data processing using SPSS 20 software that the correlation coefficient two variables is 0.46.6%.. The method used in this study is deskriptif method;